The Association Between Food Insecurity and Dietary Outcomes in University Students: A Systematic Review - Shi, Yumeng; Davies, Alyse; Allman-Farinelli, Margaret (Journal of the Academy of Nutrition and Dietetics, 2021)
University students may experience a high prevalence of food insecurity. The impacts of food insecurity on dietary intake and meal patterns of students have not been fully researched. This systematic review aimed to examine the association between food insecurity and dietary outcomes among university students. Nine electronic databases and gray literature were searched from their inception to July 2020. Studies that reported dietary outcomes in both food-secure and -insecure students or the association between food insecurity and dietary outcomes among current students in tertiary education settings in any country were included. All study designs were eligible for inclusion, except qualitative studies. Two reviewers completed the screening, data extraction, and quality assessment independently. Study quality was assessed using the Joanna Briggs Institute appraisal tools. Sixteen studies were included in the final qualitative synthesis of this review. Most studies were cross-sectional designs and of fair quality. The prevalence of food insecurity among university students ranged from 21% to 82% across studies. Lower intakes of healthy foods (eg, fruits, vegetables, and whole grains) and higher intakes of unhealthy foods (eg, fast foods, added sugars, and sugar-sweetened beverages) were observed in food-insecure students, and studies with the most representative samples of the student body found these trends. Some food-insecure students consumed breakfast and evening meals less frequently than food-secure students but the evidence was limited. Validated food security and dietary assessment tools were inconsistently used to assess diet quality among students with differing food security status. The heterogeneity of student sampling and data collection may contribute to inconsistent findings. Poorer dietary outcomes were found in university students with food insecurity compared with food-secure students, but statistical significance was only observed in a small number of studies. Future longitudinal studies using food security and dietary assessment tools validated in this population are recommended to confirm the observed associations between food insecurity and diet quality among university students.